2021
DOI: 10.3390/cimb43020066
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Apoptotic Induction and NFκB Suppression by Dammarolic Acid: Mechanistic Insight into Onco-Therapeutic Action of an Aglycone Asiaticoside

Abstract: Prostate cancer (PCa) is addressed as the second most common form of onco-threat worldwide and is usually considered as the major cause of mortality in men. Recent times have seen a surge in exploration of plant-derived components for alternative therapeutical interventions against different oncological malignancies. Dammarolic acid or Asiatic acid (AsA) is an aglycone asiaticoside that has been reported for its efficacy in several ailments including cancer. The current study aimed to investigate the anti-prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…1A and 1B, a , a high green fluorescence intensity was noted in the DS-iPSCs. The quantification of green fluorescence intensity was analyzed by ImageJ ( Alafnan et al, 2021 ), and the results suggested that the contents of ROS were increased 2.24-fold in DS-iPSCs (0.076 ± 0.004 vs 0.034 ± 0.003; P < 0.0001). The ATP contents in DS-iPSCs were 1.68-fold lower than those in N-iPSCs (3.95 ± 0.39 vs 6.64 ± 0.17; P = 0.0029) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A and 1B, a , a high green fluorescence intensity was noted in the DS-iPSCs. The quantification of green fluorescence intensity was analyzed by ImageJ ( Alafnan et al, 2021 ), and the results suggested that the contents of ROS were increased 2.24-fold in DS-iPSCs (0.076 ± 0.004 vs 0.034 ± 0.003; P < 0.0001). The ATP contents in DS-iPSCs were 1.68-fold lower than those in N-iPSCs (3.95 ± 0.39 vs 6.64 ± 0.17; P = 0.0029) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that the expression levels of almost all the genes related to mitochondrial function were downregulated in DS-iPSCs, suggesting that mitochondria were dysfunctional in these cells (Qiu et al, 2017) was analyzed by ImageJ (Alafnan et al, 2021), and the results suggested that the contents of ROS were increased 2.24-fold in DS-iPSCs (0.076 ± 0.004 vs 0.034 ± 0.003; P < 0.0001). The ATP contents in DS-iPSCs were 1.68-fold lower than those in N-iPSCs (3.95 ± 0.39 vs 6.64 ± 0.17; P = 0.0029) (Fig.…”
Section: Impaired Mitochondrial Function Is Observed In Ds-ipscsmentioning
confidence: 95%
“…Thus, it may be concluded that due to the decrease in cyclinD1 and CDK4 expression, Cur-B would have also resulted in limiting the progression of PC-3 cells at the G0/G1 phase, further explaining the anticancer efficacy of Cur-B against PC-3 cells. Contrastingly, CDK inhibitors or CDKIs such as p21Cip1 and p27Kip1 have also been reported for their regulatory role in restraining the entry of cells in the S phase of the cell cycle by impeding the kinase activity of complexes formed between cyclins and CDKs [ 32 , 37 ]. We also found that p21Cip1mRNA levels were significantly increased, thereby subsequently affirming the notion that Cur-B would have also resulted in limiting the progression of PC-3 cells at the G0/G1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…Instigation of apoptosis within PC-3 cells exposed to Cur-B at stated concentrations was assessed by acridine orange (AO) and ethidium bromide (EtBr) as earlier reported [ 14 , 37 ]. Approximately 5 × 10 5 PC-3 cells/well were incubated overnight for adherence in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxicity of C. asiatica extracts and its characteristic compound Asiatic acid-also known as dammarolic acid (Figure 2)-have been reported to induce apoptosis in PC3 cells (20-80 µM, 24 h), with an increase in intracellular ROS and activity of caspase-3 as well as nuclear fragmentation [232]. In addition, this compound has been previously reported to deploy cytotoxicity to other tumor cells.…”
Section: Centella Asiatica (L) Urbmentioning
confidence: 97%